Synthesis of biodiesel using the Mg/Al/Zn hydrotalcite/SBA-15 nanocomposite catalyst - Prabu, Marimuthu; Manikandan, Marimuthu; Kandasamy, Prabu; Kalaivani, P. R.; Rajendiran, Nagappan; Raja, Thirumalaiswamy (Acs Omega, 2019)
Biodiesel production is an enchanting and eccentric pathway for the reduction of use of fossil fuels and is procured from biologically available renewable sources such as oils and fats. A novel Mg/Al/Zn-based hydrotalcite/SBA-15 composite material having a high catalytic activity was developed and investigated for the transesterification of vegetable oil. The rationally developed composites were systematically characterized and assessed in the transesterification of soybean oil in the presence of methanol. The physicochemical evaluation of the nanocomposites demonstrated the influence of Zn in the textural characteristics, density of the basic sites, and successively the catalytic activity. The catalytic efficiency of the MAZ-x/SBA-15 composite could be linked with the basic site density determined by the temperature-programmed desorption of CO2. Among all the composites used, the MAZ-1/SBA-15 nanocomposite showed the highest activity for biodiesels, with a yield of around 90% under economical reaction conditions. The catalytic studies conferred that the fatty acid methyl ester yield is significantly influenced by various experimental conditions such as the catalyst molar ratio, reaction temperature, pressure, and contact time. It was also found that the incorporation of hydrotalcite into SBA-15 pore channels can enhance the catalyst efficiency and stability of the nanocomposite. Moreover, under mild reaction conditions, a remarkably stable catalytic performance was achieved for more than 200 h of time on stream with no catalyst deactivation.

Sustainable CO2 reduction on in (2)O(3 )with exclusive CO selectivity: catalysis and in situ valence band photoelectron spectral investigations - Mhamane, Nitin B.; Chetry, Sibo; Ranjan, Ravi; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2022)
This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H-2 ratios exhibit 98-99.6% CO selectivity with 25-38% CO2 conversion between 773 and 873 K. CO2 and H-2 conversion under steady-state conditions at 773-873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H-2 feed) on the catalyst surface, underscoring the presence of an ideal reactant composition for the reverse water-gas shift reaction, while H-2-rich feed compositions show the H-2-dominated surface. Surface electronic structure changes, under near-operating conditions, were explored with near ambient pressure photoelectron spectroscopy (NAPPES), and the interesting findings are as follows: (a) A shift in the valence band to lower binding energy, up to 0.6 eV, was observed because of electron filling at high temperatures. (b) An observation of heterogeneous nature of the catalyst surface under NAPPES measurement conditions is attributed to the generation of active oxygen vacancy (O-v) sites, which in turn changes the work function of In2O3. (c) The above changes are found to be reversible, when the reaction was stopped. Vibrational features of the reactant molecules were observed to be broadened in the active temperature window of the catalyst supporting the heterogeneous character of the catalyst surface because of dynamic O-v generation. By optimizing gas hourly space velocity, CO2:H-2 ratio, and reaction temperature, exclusive CO selectivity is possible with a H-2:CO2 ratio of similar to 0.67, which will avoid the product separation stage altogether, while minimizing the expensive H-2 in the reactant feed.
Keywords: heterogeneous catalysis; Oxygen vacancy; photoelectron spectroscopy; RWGS; Work function